Electrical performance and interface states studies of undoped and Zn-doped CdO/p-Si heterojunction devices - Farag, A. A. M.; Cavas, M.; Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2012)
A transparent semiconducting layer of CdO thin film was grown on p-type Si substrates to fabricate Zn-doped CdO/p-Si heterojunction devices using sol-gel spin coating method. The current density-voltage characteristics (J-V) of the undoped CdO/p-Si and Zn-doped (at 1%, 2%, 3% and 4%) CdO/p-Si diodes were measured at room temperature. The dark J-V characteristics of the diodes show rectification behavior. The rectification ratio of the diodes is found to be dependent on both applied voltage and the doping ratio of Zn. At lower voltages, the current in the forward direction obeys the thermionic emission process. For relatively higher voltages, the current is dominated by a space charge limited conduction mechanism. Under reverse bias conditions, the J-V characteristics of the diodes can be interpreted using Schottky mechanisms. The important junction parameters such as series resistance (R-s), the shunt resistance (R-sh), the ideality factor (n) and the barrier height (Phi(b)) were determined by performing different plots from the forward bias J-V characteristics. The corrected capacitance-voltage (C-Adj-V) and corrected conductance-voltage (G(Adj)-V) characteristics were measured in the frequency range of 10 kHz to 1 MHz. It is found that the C-Adj-V and G(Adj)-Vcurves were strongly influenced with both frequency and presence of Zn-dopant content. The interface state density (D-it) is also depend on frequency and Zn-dopant content, and decreases with increasing frequency and Zn-dopant content. The obtained results indicate that the electrical properties of the CdO/p-Si heterojunction diodes are controlled by Zn-dopant content. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Heterostructures; Semiconductors; Sol-gel growth; Thin films